2008
DOI: 10.1088/0957-4484/19/9/095607
|View full text |Cite
|
Sign up to set email alerts
|

Growth of CNTs on Fe–Si catalyst prepared on Si and Al coated Si substrates

Abstract: In this paper we report the effect of Al interlayers on the growth characteristics of carbon nanotubes (CNTs) using as-deposited and plasma etched Fe-Si catalyst films as the catalysts. Al interlayers having various thicknesses ranging from 2 to 42 nm were deposited on Si substrates prior to the deposition of Fe-Si catalysts. It was found that the Al interlayer diffuses into the Fe-Si catalyst during the plasma etching prior to the CNT growth, leading to the swelling and amorphization of the catalyst. This all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…A small reduction in the particle size was anticipated, as the fly ash particles were entrained in the CNFs, hence reducing their agglomeration. Likewise, although the CNFs are known to be hydrophobic and not easily dispersed in water [45], the entrained fly ash most probably enhanced their solubility. Both of these materials were then introduced into a Dolapix polymer solution.…”
Section: Resultsmentioning
confidence: 99%
“…A small reduction in the particle size was anticipated, as the fly ash particles were entrained in the CNFs, hence reducing their agglomeration. Likewise, although the CNFs are known to be hydrophobic and not easily dispersed in water [45], the entrained fly ash most probably enhanced their solubility. Both of these materials were then introduced into a Dolapix polymer solution.…”
Section: Resultsmentioning
confidence: 99%
“…The first two methods impose problems in scaling up the production up to industrial level while the chemical vapour deposition (CVD) method offers the best hope for large scale production of CNTs. A catalyst is usually needed for the synthesis of CNTs, the most commonly used catalysts are either organo-metallic compounds such as cobaltocene, ferocene, nicklocene, or metal catalyst powder or thin films [9][10][11][12][13]. Different substrates (such as quartz, silicon wafers, alumina, aluminosilicates etc.)…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the thickness of the Al layer could be responsible for controlling the length of CNTs. [27][28][29][30] The impact was mainly attributed to the diffusion of Al into the catalyst layer leading to a decrease in the carbon solubility in the catalyst particles. As shown in the literature, the decrease in the carbon solubility resulted in shorter CNTs as the Al layer thickness increases.…”
Section: Resultsmentioning
confidence: 99%